Bulk Pt/CsPbBr3 Schottky junctions for charge boosting in robust triboelectric nanogenerators. Issue 24 (11th June 2020) - Xie, Guixiang; Yang, Xiya; Duan, Jialong; Duan, Yanyan; Tang, Qunwei
Abstract : Bulk Pt/CsPbBr3 Schottky junctions are built in a perovskite triboelectric nanogenerator to increase the short-circuit current output. Abstract : Triboelectric nanogenerators (TENGs) have attracted growing attention because they are advanced energy conversion devices to efficiently harvest low-frequency mechanical energy from nature. How to increase the permittivity of electrode materials as well as the surface charge density is technically important to improve the output performances of a robust TENG. In this study, an all-inorganic cesium lead bromide (CsPbBr3 ) perovskite film with semiconducting characteristics is combined with metallic nano-platinum to build bulk Pt/CsPbBr3 Schottky junctions, which are used as triboelectric electrode materials in vertical contact-separation perovskite TENGs. The systematic characterization demonstrates that the electron binding energy and dielectric properties of bulk Pt/CsPbBr3 Schottky junction tailored perovskite films are maximized by optimizing the Pt dosage. An open-circuit voltage of 273 V, a short-circuit current density of 30.3 μA cm −2 and an instantaneous maximum power density of 1295.5 mW m −2 are achieved by the champion Pt/CsPbBr3 TENG at a Pt dosage of 0.5%. A maximum energy storage of 3.96 mJ is stored in a 1 μF capacitor within a 300 s charging period. This work provides new insights into Schottky junction TENGs for enriching the fundamental principles of both halide perovskites and TENGs.